2017
DOI: 10.3747/pdi.2016.00041
|View full text |Cite
|
Sign up to set email alerts
|

Modified Simple Peritoneal Wall Anchor Technique (Pwat) in Peritoneal Dialysis

Abstract: ♦ BACKGROUND: Outflow obstruction, a common complication in patients with peritoneal dialysis (PD), usually results in unnecessary catheter removal or replacement. This study describes a modified simple method of anchoring a PD catheter on the anterior peritoneal wall without using a laparoscopic system (peritoneal wall anchor technique, PWAT). ♦ METHODS: We performed a retrospective cohort study of consecutive PD catheter insertions, and compared the catheter survival rate between the traditional method and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…[19,20] However catheter migration is still a big problem in peritoneal dialysis catheter insertion and therefore in recent years catheter fixation to the abdominal wall have been developed to prevent this complication. [21][22][23] In various studies disadvantages of laparoscopic peritoenal dialysis catheter insertion was reported to be; long operative time, increased costs and risks due to need of general anesthesia. [24,25] Sedation, local anesthesia, general anesthesia and regional block have been the methods used during insertion.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] However catheter migration is still a big problem in peritoneal dialysis catheter insertion and therefore in recent years catheter fixation to the abdominal wall have been developed to prevent this complication. [21][22][23] In various studies disadvantages of laparoscopic peritoenal dialysis catheter insertion was reported to be; long operative time, increased costs and risks due to need of general anesthesia. [24,25] Sedation, local anesthesia, general anesthesia and regional block have been the methods used during insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The original method of PWAT requires laparoscopic assistance or a particular device named the PWAT applicator [22,23]. Recently, a simple modified PWAT, which does not require laparoscopic assistance or special devices has been established [24]. It was reported that the modified PWAT achieved a better catheter survival rate than the traditional method by preventing catheter tip migration [24].…”
Section: Peritoneal Wall Anchor Technique (Pwat)mentioning
confidence: 99%
“…At our institution, the PD catheter is inserted at a point 3 cm cranial to the biopsy area and is then fixed to the abdominal wall using a 2-0 nylon suture under vision from the biopsy area (peritoneal wall anchor technique) ( Fig. 2g-i) [11]. The peritoneal wall anchor technique reportedly improves the catheter survival rate [10], although the catheter is blindly fixed to the abdominal wall at the area inferior to the catheter insertion in the absence of peritoneal biopsy.…”
Section: Surgical Procedures For Peritoneal Biopsy At Pd Catheter Insementioning
confidence: 99%
“…The peritoneal wall anchor technique reportedly improves the catheter survival rate [10], although the catheter is blindly fixed to the abdominal wall at the area inferior to the catheter insertion in the absence of peritoneal biopsy. However, in addition to the aforementioned advantage [11], the present method employing biopsy area allows for the fixation of the catheter to the abdominal wall in a safe and simple manner.…”
Section: Surgical Procedures For Peritoneal Biopsy At Pd Catheter Insementioning
confidence: 99%